Pemberian Aromaterapi Lavender terhadap Kualitas Tidur Pasien Hemodialisis - Hartati, Yeni; Nursanti, Irna; Irawati, Diana; Natashia, Dhea; Hasanah, Uswatun (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effectiveness of lavender aromatherapy on hemodialysis patients' sleep quality. The method used is experimental intervention twice a week for four weeks. Before and after the intervention, sleep quality will be measured using the PSQI (Pittsburgh Sleep Quality Index) instrument. The results showed that (t = 22.789, p = 0.0001). 7.3% of the variable variation in the model was able to explain changes in the percentage of sleep quality (R2=0.073). Education variables (β=0.240, p=1.888), duration of HD (β=0.227, p=1.583), and the variable that is a predictor of sleep quality is gender (β=-0.006, p=0.421). In conclusion, there is a relationship between giving lavender aromatherapy and the sleep quality of hemodialysis patients compared to patients who did not receive lavender aromatherapy. Keywords: Lavender Aromatherapy, Hemodialysis, Sleep Quality